Interferência da idade na progressão de parkinsonismo no modelo da reserpina em ratos - Melo, João Eduardo Conceição (2020)
Parkinson's disease (PD) is the second most prevalent neurodegenerative disease in the world, being more common in the elderly population. Studies in animal models have contributed to the understanding the pathophysiology of this disease. Although PD is related to aging, but animal models used for scientific research to investigate the progression of the disease are young animals. In this sense, the aim of the study was to evaluate the effect of age on the model of parkinsonism induced by reserpine (RES) in rats. Male rats, aged 6-8 (adult) or 18-24 (elderly) months, were divided into 6 groups: control-elderly (CI) (n=7), reserpine-elderly (RI) (n=6), reserpine-elderly abstinence (RI-ABS) (n=6) controladult (CA) (n=7), reserpine-adult (RA) (n=6) and reserpine-adult abstinence (RAABS) (n=6). The animals received 15 injections of RES (0.1 mg / kg) or vehicle on alternate days, throughout the experiment, were subjected to behavioral tests: (1) catalepsy test, every 48 hours and (2) general activity in the open field, 24 hours after the 2 injection and weight assessment, every 4 days. On the 30th day after the beginning of the experiment, half of the animals in the RI and RA groups were randomly selected and killed, while the remaining animals were sacrificed on the 60th (abstinence animals) and underwent the same procedures. During this period, the administration of RES was suspended. The brains of all animals were processed, following standard procedure for immunohistochemistry for tyrosine hydroxylase (TH) in the substance nigra (SN), dorsal striatum (STR) and ventral tegumentar area (ATV). RES animals showed longer time in the bar, in the catalepsy test from day 18 (p=0.0010) to day 42 (p=0.0048) for RA animals compared to CA and day 12 (p=0.0051) on day 46 (p=0.0050) for the RI animals. RI animals also had a longer catalepsy time compared to RA animals between days 12 (p=0.0399) and day 36 (p=0.0154). RES induced weight loss when compared to its controls, for the RA group the difference appeared on day 12 (p=0.0249) and remained until day 48 (p=0.0316), for the RI group the difference appeared on day 16 (p=0.0365) and remained until the end of the experiment on day 60 (p=0.0416). In the open field, there was no effect of RES on the evaluated parameters. Animals in the RA and RI groups showed decreased markings for TH in SNpc (p=0.0009 and p=0.0032, respectively) and STR (p=0.0026 and p=0.0043, respectively) when compared to their respective controls. In the ATV, only the RA animals showed a decrease in TH marking when compared to the CA (p=0.0166). The decrease in TH was not reversible in SN (p=0.0161) and STR (p=0.0086) for animals in the RI group. Thus, the study found a greater effect of RES on elderly animals compared to adults, since we observed a greater increase in the time of catalepsy in those, non-recovery of weight with the cessation of the intervention and non-recovery of concentrations of TH in motor areas in elderly animals.